Prevention of lymphoedema - Ochałek, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2011)
Lymphoedema (lymphoedema), which is understood to be a result of mechanical (low output) failure of the lymphatic system, may be a result of abnormalities of structure and function of the lymphatic system (primary lymphoedema), injuries, inflammation, chronic vein insufficiency or related to cancer (secondary lymphoedema). Because of the chronic nature of the illness and the lack of possibilities to be cured, education and prevention play an important role. The purpose of this paper is to present a current review of using prophylactic methods in the prevention of lymphatic insufficiency.